Perfil do exoproteoma e identificação de proteínas imunogênicas secretadas por Staphylococcus saprophyticus - Oliveira, Lucas Silva de (2014)
Staphylococcus saprophyticus is characterized as uropathogenic bacteria that causes urinary tract infections especially in young women. Some virulence factors were elucidated, however, little is known about how this bacteria install itself at host human. The urease was the first virulence factor described in S. saprophyticus, being responsible by increasing of the bladder pH in infected patients. This is the first study about S. saprophyticus in proteomics and immunoproteomics perspective of the secreted proteins (exoproteome) of this bacterium. A total of 44 new secreted proteins were detected by mass spectrometry. Among the proteins found, five of them have a crucial role in the glycolytic pathway: Triosephosphate isomerase (TPI), enolase (ENO), Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) and Glucose-6-phosphate isomerase (GPI), however, its role as moonlighting proteins have been observed in various microorganisms. Through of the immunoproteomics, it was possible to detect 18 protein species that reacted onto Western-blotting, and 5 of them could be identified by mass spectrometry. The most abundant protein specie identified as immunogenic in S. saprophyticus, it was transglycosilase IsaA (Immunodominant staphylococcal antigen A), being it well described in Staphylococcus aureus as virulence factor. Another abundant protein found as immunogenic was Ssa (Staphylococcal secretory antigen), which, it was identified under 3 isoforms. The enolase was the last protein identified at immunoproteome of S. saprophyticus. It was possible to conclude from these results that S. saprophyticus has a wide of extracellular proteins capable to promote bacteria adaption, and some of them are involved in oxidative/nitrosative stress (SOD and AhpC), besides possess proteins that have the capacity to incite the humoral immune response in BalbC mice. All this lead us to hypothesize that S. saprophyticus have defense and virulence mechanisms in order to protect itself against extracellular stresses and appropriate mechanisms to promote urinary tract infections.